2012
DOI: 10.1111/j.1468-3083.2012.04551.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of basal cell carcinoma in high definition optical coherence tomography: en‐face and slice imaging mode, and comparison with histology

Abstract: Background Optical coherence tomography (OCT) allows real-time, in vivo examination of basal cell carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 21 publications
3
82
2
2
Order By: Relevance
“…20,21 Fourier Domain OCT showed epidermal thinning, superficial crusting and rarefaction of the hair follicles; these features have not been described in HD-OCT reports. [14][15][16] In keeping with our results, HD-OCT investigations have shown epidermal disarray in en-face scans and destruction of layering of the epidermis and dermis in slice mode scans with similar detection rates between the two imaging modes. [14][15][16] The original OCT diagnostic criteria for BCC lesions were described by Olmedo et al using conventional OCT. 11 In our study, Fourier domain imaging showed dark lobular patterns of BCC nests and bright margins of collagen compression in 100%; decreased reflectance at the borders of the lobules was seen in 73% of the lesions, whereas dilated blood vessels were detected in only 33%, in keeping with previous studies.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…20,21 Fourier Domain OCT showed epidermal thinning, superficial crusting and rarefaction of the hair follicles; these features have not been described in HD-OCT reports. [14][15][16] In keeping with our results, HD-OCT investigations have shown epidermal disarray in en-face scans and destruction of layering of the epidermis and dermis in slice mode scans with similar detection rates between the two imaging modes. [14][15][16] The original OCT diagnostic criteria for BCC lesions were described by Olmedo et al using conventional OCT. 11 In our study, Fourier domain imaging showed dark lobular patterns of BCC nests and bright margins of collagen compression in 100%; decreased reflectance at the borders of the lobules was seen in 73% of the lesions, whereas dilated blood vessels were detected in only 33%, in keeping with previous studies.…”
Section: Discussionsupporting
confidence: 75%
“…[14][15][16] The original OCT diagnostic criteria for BCC lesions were described by Olmedo et al using conventional OCT. 11 In our study, Fourier domain imaging showed dark lobular patterns of BCC nests and bright margins of collagen compression in 100%; decreased reflectance at the borders of the lobules was seen in 73% of the lesions, whereas dilated blood vessels were detected in only 33%, in keeping with previous studies. 15,18 The additional feature of central necrosis was observed in 20% of lesions and suggested the BCC growth pattern with fast progressive enlargement outgrowing the tissue blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations